Nitrosyl isomerism in amorphous Mn(TPP)(NO) solids - Kurtikyan, Tigran S; Hayrapetyan, Vardan A; Martirosyan, Garik G; Ghazaryan, Robert K; Iretskii, Alexei V; Zhao, Hailiang; Pierloot, Kristine; Ford, Peter C (Chemical communications (Cambridge, England), 2012)
Reaction of NO with amorphous Mn(TPP) layers gives two Mn(TPP)(NO) isomers with linear and bent Mn-N-O geometries that reversibly interconvert with changes in temperature. DFT computations predict that the linear complex is the singlet ground state while the bent structure is a triplet state.